Hereditary spherocytosis with successful splenectomy in a pregnant black South African lady: a case report - Elmezughi, Khaled (Pan Afr Med J, 2019)
Hereditary spherocytosis is a rare cause of chronic haemolytic anaemia. It is rarer in the black population with extremely few cases reported. Initial assessment of a patient with suspected disease should include documenting clinical features of chronic haemolysis and a family history. Its management in pregnancy is challenging and needs a multidisciplinary team. We report on a black South African woman with hereditary spherocytosis and massive splenomegaly presenting with severe haemolytic anaemia at 23(rd) week of pregnancy. She had a successful splenectomy.